Options for CO2 Sequestration in Kuwait. (July 2017) - Neele, Filip; Vandeweijer, Vincent; Mayyan, Haya; Sharma, Shashank Rakesh kumar; Kamal, Dawood
Abstract: In preparation for future requirements to abate CO2 emission levels, a CO2 storage feasibility study was carried out for the country of Kuwait. At present, no definite plans exist to install capture facilities at the larger emission points in the country; the study presented is one of the first steps to prepare the country for a low-carbon future. The first step was to investigate formations for potential CO2 storage capacity in a country-wide screening. Two regions within Kuwait were shortlisted for subsequent evaluation; one site was selected for detailed characterization and assessment. The main result of the study was that the Kra Al-Maru Trend is likely to be a first-class CO2 storage site. Pending verification of the findings we conclude that the Kra Al-Maru Trend provides the storage capacity of at least 440 Mt, which is equivalent to the CO2 produced in a period of 40 years by the Doha East and Doha West power plants combined. The subsurface of the Kra Al-Maru Trend can store this CO2 at the rate that is currently emitted to the atmosphere by the two power plants. No showstoppers were discovered to safe and secure storage of CO2 . Storing CO2 in the subsurface of the Kra Al-Maru Trend offers the possibility of future back-production of the CO2 stored. Verification of these conclusions is required, through a dedicated appraisal well that targets the Cretaceous interval at depths between about 2000 m and 3000 m (6000 - 9000 ft).